INTERELASI DAN INTERAKSI KAWASAN KAMPUS PERGURUAN TINGGI DI KOTA YOGYAKARTA - H, Sumarjo (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
ABSTRACT The purpose of this research is to find a theory model of interrelationship theory between campus region with its environment, and the interaction between campus group that located in the city with other group that located in the urban fringe of Yogyakarta. The sampling of this research has taken purposively, campus group that located in the city consist of UGM, UNY, USD 1, UAJ and UII 1. Other group that located in the urban fringe represented by UPN, STIE, U1I2, USD 2 and STIPER. Analisys of the data that already taken has decided to use quantitative method. The result of this research indicates there are significant interrelationship between campus region with its environment, with relationship frequency 74% and 80%. The interaction between campus group that located in the city with other group that located in the urban fringe of Yogyakarta seem equal, so it can be concluded that the relationship formed in concentric pattern. Keywords: interrelation, interaction, campus region